The figure of the influencer under scrutiny: highly exposed, poorly regulated - González-Díaz, Cristina; Quiles-Soler, Carmen; Quintas-Froufe, Natalia (Frontiers in Communication, 2024)
The figure of the influencer has generated an increase in their presence on social networks. Their ability to create content, their credibility and their identification with the consumer represent an added value in commercial communication. However, their disclosures are controversial due to the lack of transparency and differentiation between their commercial and opinion content. The absence of a clear definition of an influencer, the need to regulate their actions and the difficulty of identifying the commercial content of their publications are evidence of the concern to regulate their activity. The aim of this paper is to analyze, in the European context, the specific regulations on commercial disclosures by influencers, as well as to ascertain the point of view of the agents involved. To this end, a content analysis of the guidelines, regulations and/or laws of 24 European Union countries is carried out, complemented by an ad hoc questionnaire that brings together different aspects that can be defined and delimited. The results show a lack of unanimity in the rules and regulations governing influencers, as well as a manifest concern on the part of professionals in the sector to determine their communications. Only two countries, France and Spain, have specific legislation on the subject, limiting commercial disclosure to the existence of consideration and/or number of followers. It is clear that the existing guidelines are, in most cases, more comprehensive in terms of transparency guidelines for identifying advertising than the regulatory texts. The findings question whether the path of legislation is the right one, or whether efforts should instead focus on media and advertising literacy for both influencers and consumers.